Identity Negotiation in Street Musical Performances of Kemi Special: A Sociostylistic Perspective - Sarat Salihu-Abdulakeem; Janet Bamitale Balogun; Mariam Titilope Olugbodi (University of Chitral Journal of Linguistics and Literature, 2025)
Identity construction and negotiation are central to most discussions surrounding the feminist ideology. Scholars, literary critics, and professionals across diverse areas of human callings have, over the years, contributed to this discussion to bridge the gender gap. Despite the existence of a myriad of dialogues on feminism, the gaps in culturally defined roles and expectations of males and females within the African context still prevail. Therefore,  identity negotiation is still an order of the day. This paper examines how Kemi Special negotiates feminist identity in her musical performances on the street through the lenses of sociolinguistics and stylistics. The data for this study, constituting purposively selected songs from musical performances of Kemi Special, were analysed using Tajfel & Turner’s Social Identity Theory (SIT). Also, stylistic features that are inherent in the songs are analysed. The study found that the music artiste deploys sociostylistic features constituting specific word classes, street jargons, neologisms, declaratives, analogy, and eulogy. Through the deployment of the sociostylistic features, Kemi identifies with the strengths of womanhood. She portrays these strengths as the drivers of female socio-economic and political existence amidst adversaries.